Anatomical variations of the human mandible and prevalence of duplicated mental and mandibular foramina in the collection of the State University of Londrina - Marna Eliana Sakalem; Camila Salvador Sestario; Alisson Luiz Motta; Dayanna Quintilhano; Suzana Lopes Myszynski; Vinicius Antonio Hiroaki Sato (Elsevier, 2024)
Background: The knowledge of the morphology of the human mandible is essential for diverse dental procedures. The potential anatomical variations of the bone, including the presence of accessory foramina, may culminate in significant clinical outcomes and implications, directly impacting dental surgery and anesthesia. Aim of study: This study aimed to evaluate the general morphology of human mandibles in the collection of the State University of Londrina, South Brazil, and to determine the presence of anatomical variations. Materials and methods: A total of 63 mandibles were measured bilaterally with a pachymeter for various dimensions, and a proportional calculation of each parameter was obtained, based on the size of the length of each mandibular base. In addition to the general descriptive morphology of the mandibles, considering that six mandibles presented duplicated foramina, they were divided into two groups, and the mandibles with no anatomical variation (normal group, N = 57) were compared to those with duplicated foramina (N = 6). Data were checked for normal distribution and then tested statistically. Results: Six out of 63 mandibles (9.52 %) presented duplicated foramina, either mental or mandibular. Significant differences between the normal group and the duplicated foramina group were found in the lengths between mandibular angle and condylar process on both sides (right: 65.14 mm vs. 74.91 mm, p = 0.001; left: 65.04 mm vs. 72.34 mm, p = 0.019); between mandibular angle and coronoid process on the right side (59.55 mm vs. 67.67 mm, p = 0.007); and in the diameter of the left mandibular foramen (3.71 mm vs. 4.64 mm, p = 0.04), with the duplicated foramina group presenting a higher average for all parameters. Conclusion: These findings provide a morphological pattern for the Department of Anatomy of the State University of Londrina collection and highlight the presence of anatomical variations of the human mandible, specifically regarding duplicated foramina. The presence of accessory mental and mandibular foramina is clinically significant for dental procedures, potentially impacting the anesthesia. Understanding these variations is crucial for dental surgeons to prevent complications. Future research should further explore the functional implications and clinical significance of these variations.